Developing a hospital quality improvement initiative in Lesotho. Issue 1 (4th February 2014) - Berman, Joshua; Limakatso Nkabane, Elizabeth; Malope, Sebaka; Machai, Seta; Jack, Brian; Bicknell, William
Abstract : Purpose: – Hospital-based quality improvement (QI) programs are becoming increasingly common in developing countries as a sustainable method of strengthening health systems. The aim of this paper is to present the results and lessons learned from a QI program in a large, rural, district hospital in Lesotho, Southern Africa. Design/methodology/approach: – Over a 15-month period, a locally-relevant, hospital-wide QI program was developed and implemented. The QI program consisted of: planning meetings with district and hospitals staff; creation of multi-disciplinary QI teams; establishment of a QI steering committee; design and implementation of a locally appropriate QI curriculum; and monthly consultation from technical advisers. Initial QI programming was developed in three distinct areas: maternity care, out-patient care, and referral systems. Findings: – Partogram documentation in the maternity department increased by 78 percent, waiting time for critically ill patients in the out-patient department was reduced by 84 percent, and emergency referral times were reduced by 58 percent. Originality/value: – The design and early implementation of QI programs should focus on easily achievable, locally-relevant improvement projects. It was found that early successes helped to fuel further QI gains and the authors believe that the work building sustainable QI skill sets within hospital staff could be useful in the future when attempting to tackle larger national-level quality of care indicators. The findings add to the existing evidence suggesting that an increased use of locally-relevant quality improvement programming could help strengthen health care systems in low resource settings.